PENGARUH PENYALURAN DANA ZAKAT, INFAK, SEDEKAH, UPAH MINIMUM PROVINSI DAN KEMISKINAN TERHADAP INDEKS PEMBANGUNAN MANUSIA DI INDONESIA - Lestari, Dewi (Jurnal Ekonomi Syariah Darussalam, 2023)
This paper discusses the review of Islamic law on the contract to rent a motorized trishaw in the Village of Beetle Indah, Badar Sub-district, Southeast Aceh district. The author is interested in conducting this research to obtain an overview of the contract for renting a motorized trishaw which is a public vehicle for which there is no standard fixed rate, so it will be reviewed from the perspective of Islamic law. To get answers to research problems, the author conducts research using field research methods which have a starting point on descriptive qualitative. This research is about leasing contracts Motorized rickshaws are related to both parties, namely the lessor (motorized rickshaw owner) and the renter (the rickshaw passengers), in this case all good explanations are needed regarding the distance to be traveled and the costs agreed by both parties. because renting only uses the function or benefits of the goods or objects being rented out without owning the goods or objects, so the motorbike rickshaw still belongs to the person who rents it but the benefits are used by the person who rents it by providing compensation in the form of fees provided that the distance traveled.